Predictions Of Psychological Preparedness And Wellbeing Amongst Youth Entrepreneurs In Africa - Olubiyi, Timilehin; Folake Olubunmi , Lanre- Babalola; Olufemi Samuel, Omoyele; Grace Oluwatoyin , Obadare; Callistus Destiny, Odeh (Cattleya Darmaya Fortuna, 2024)
In recent years, there has been a significant increase in the interest of academics in the field of entrepreneurship and business towards wellbeing. In particular, young people are very vulnerable to poverty at the global level, so entrepreneurship among youth is a major focus. Successful entrepreneurship requires mental and physical well-being to start a business. This study aims to explore psychological readiness and well-being in achieving entrepreneurship among youth in Nigeria, the most populous country in Africa. This research was conducted by selecting 150 Micro, Small and Medium Enterprises (MSMEs) run by young entrepreneurs using a convenient sampling technique. The types of MSMEs studied include furniture makers, pubs, restaurants, spas, hair salons and traders. Data was collected through a questionnaire prepared with a four-point Likert Scale and analyzed using descriptive statistics, including frequencies and percentages. The results show that most young Nigerians have many abilities, but fear of failure, deception, and reluctance to show weakness prevent them from trying. Youth also face pressure from society that expects them to be better, which encourages them to set up businesses. This research concludes that entrepreneurship training for youth can increase psychological resilience and mental readiness. Therefore, it is important for young entrepreneurs in Nigeria and Africa to get psychological preparation, as psychological well-being contributes to physical health. This research recommends that the environment in which youth develop and implement entrepreneurial ventures be made more welcoming and supportive, with government policies that attract adequate attention and participation.